2014
DOI: 10.1093/mnrasl/slu108
|View full text |Cite
|
Sign up to set email alerts
|

Deep spectroscopic luminosity function of Abell 85: no evidence for a steep upturn of the faint-end slope

Abstract: We present a new deep determination of the spectroscopic LF within the virial radius of the nearby and massive Abell 85 (A85) cluster down to the dwarf regime (M* + 6) using VLT/VIMOS spectra for ∼ 2000 galaxies with m r 21 mag and µ e,r 24 mag arcsec −2 . The resulting LF from 438 cluster members is best modelled by a double Schechter function due to the presence of a statistically significant upturn at the faintend. The amplitude of this upturn (α f = −1.58 +0.19 −0.15 ), however, is much smaller than that o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(73 citation statements)
references
References 47 publications
8
64
1
Order By: Relevance
“…There are only a handful of deep, spectroscopic observations of nearby clusters, in which cluster-to-cluster variations of the shape of the LF are observed: Virgo and Abell 2199 LFs do not show any upturn at the faint end (Rines & Geller 2008), unlike A 85 (Agulli et al 2014). Moreover, the radial analysis of Rines & Geller (2008) does not present a significant dependence of the LF on clustercentric radius, but opposite trends in the radial variation of M * between Virgo and Abell 2199.…”
Section: Environmental Influence On Dwarfsmentioning
confidence: 94%
See 1 more Smart Citation
“…There are only a handful of deep, spectroscopic observations of nearby clusters, in which cluster-to-cluster variations of the shape of the LF are observed: Virgo and Abell 2199 LFs do not show any upturn at the faint end (Rines & Geller 2008), unlike A 85 (Agulli et al 2014). Moreover, the radial analysis of Rines & Geller (2008) does not present a significant dependence of the LF on clustercentric radius, but opposite trends in the radial variation of M * between Virgo and Abell 2199.…”
Section: Environmental Influence On Dwarfsmentioning
confidence: 94%
“…We computed the total spectroscopic LF of A 85 following the prescription in Agulli et al (2014). The LF is given by: φ(Mr) = N phot (Mr) × fm(Mr)/(∆Mr × A), where N phot is the number of photometric targets (see section 2.2), fm the fraction of cluster members defined in section 2.3, A the surveyed area and ∆mr = 0.5 the magnitude bin size used.…”
Section: Spectroscopic Lf Of a 85mentioning
confidence: 99%
“…Nevertheless, it requires a large amount of observational time and generally larger telescope apertures than the photometric one. This method has mainly been applied to the study of nearby individual clusters (e.g., Rines & Geller 2008;Agulli et al 2014). The photometric method requires less observing time and consists in computing the galaxy number counts, as a function of magnitude, within the system region and in a region of the sky in which no structure is present.…”
Section: Luminosity Functions Of Individual Systemsmentioning
confidence: 99%
“…Within this framework, the progenitors of early-type dwarf galaxies would be dwarf systems with active star formation that was quenched by the sweeping out of their cold gas content by the interaction of the galaxy with the hot intracluster medium (see Boselli et al 2008;Gavazzi et al 2010). The lines of observational evidence for this argument include (i) the similar faint-end slope of the galaxy luminosity function observed in nearby galaxy clusters and the field (see e.g., Boselli et al 2011;Agulli et al 2014); (ii) the relation of the gas content, colour, and environment found in clusters (e.g. Sánchez-Janssen et al 2008;Gavazzi et al 2013); (iii) the age and metallicity spread observed in dwarf galaxies of nearby clusters, together with the correlation between age, metallicity, and clustercentric distance (see Boselli et al 2008;Smith et al 2009;Toloba et al 2009;Koleva et al 2013); the globular cluster content (see Sánchez-Janssen & Aguerri 2012); and the different kinematics properties between galaxies located in the inner and the outermost regions of the clusters (see Toloba et al 2009).…”
Section: Introductionmentioning
confidence: 96%
“…In contrast, red dwarf galaxies dominate in number the faint end of the luminosity function of galaxies in nearby clusters (e.g. De Propris et al 2003;Popesso et al 2006;Agulli et al 2014).…”
Section: Introductionmentioning
confidence: 99%